Expanded genetic codes in next generation sequencing enable decontamination and mitochondrial enrichment. - Kevin J McKernan; Jessica Spangler; Lei Zhang; Vasisht Tadigotla; Stephen McLaughlin; Jason Warner; Amir Zare; Richard G Boles (PLoS ONE)
We have developed a PCR method, coined Déjà vu PCR, that utilizes six nucleotides in PCR with two methyl specific restriction enzymes that respectively digest these additional nucleotides. Use of this enzyme-and-nucleotide combination enables what we term a "DNA diode", where DNA can advance in a laboratory in only one direction and cannot feedback into upstream assays. Here we describe aspects of this method that enable consecutive amplification with the introduction of a 5th and 6th base while simultaneously providing methylation dependent mitochondrial DNA enrichment. These additional nucleotides enable a novel DNA decontamination technique that generates ephemeral and easy to decontaminate DNA.